2019
DOI: 10.29333/iejme/6278
|View full text |Cite
|
Sign up to set email alerts
|

Grade 11 Students’ Proof Construction Ability in Relation to Classroom Resources

Abstract: Despite proof being fundamental to the mathematics discipline and its role as a means to convey mathematical content, little is known about the effect of resources on influencing students' proof construction ability. The purpose of this study was to compare two didactic environments, one regarded as resourced (favored) and the other under-resourced (disadvantaged), in relation to the construction of a mathematical proof. Motivated by the discrepancies in the literature on the influence of school resources on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Finally, we think it is important to bear in mind the findings of Shongwe (2020), who also worked in a South African context. Shongwe found that so-called proof ability was not evenly distributed across various schools but that students in well-resourced, high-socioeconomic-status schools were found to be more adept at proving than students in under-resourced, lowsocioeconomic-status schools.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we think it is important to bear in mind the findings of Shongwe (2020), who also worked in a South African context. Shongwe found that so-called proof ability was not evenly distributed across various schools but that students in well-resourced, high-socioeconomic-status schools were found to be more adept at proving than students in under-resourced, lowsocioeconomic-status schools.…”
Section: Discussionmentioning
confidence: 99%
“…Third, given many of the current systems of education that function as societal gatekeepers, proof instruction can exacerbate the role that mathematics plays in inequitably sorting and excluding students from future opportunities. In South Africa, for example, Shongwe (2020) found that greater school resources correlated with greater proof performance. This suggests that a danger of instituting proof for all would be that differential success with proving could be used as a status symbol and yet it is actually a reflection of the differential resources allotted to schools.…”
Section: Calls For Students To Learn Proving In Schoolmentioning
confidence: 99%
See 1 more Smart Citation